Methodik zum Aufbau einer Entwicklungsumgebung für die datengetriebene Gestaltvorhersage von Bauteilen - Ott, Manuel
Die effiziente Nutzung von Ressourcen ist in der modernen Produktentwicklung von zentraler Bedeutung, nicht nur im Hinblick auf Materialien, sondern auch angesichts des Fachkräftemangels. Dabei sollten menschliche Arbeitskräfte gezielt eingesetzt und unnötige Iterationen zwischen Abteilungen vermieden werden, wobei die Kommunikation zwischen Konstruktion und Berechnung eine entscheidende Rolle spielt. Im Rahmen dieser Arbeit wird eine Methode entwickelt, die es Konstrukteuren ermöglicht, mithilfe künstlicher neuronaler Netze schnell mechanisch optimierte Bauteilgeometrien vorzuschlagen und so Korrekturschleifen zu minimieren. Hierfür wird eine Entwicklungsumgebung analysiert, die die Integration neuronaler Netze in bestehende Konstruktions- und Optimierungsprozesse erlaubt, einschließlich der Definition von Eingaben, Ausgaben, Datenformaten, Datensätzen und Schnittstellen zu kommerzieller Software. Zur Sicher-stellung der generalisierten Nutzbarkeit der Trainingsdaten werden Bauteilgeometrien zunächst mithilfe geometrischer Primitive abstrahiert und anschließend zu Gesamtgeometrien zusammengesetzt. Die Machbarkeitsstudie zeigt, dass mechanisch optimierte Bauteilgeometrien auf diese Weise erfolgreich vorhergesagt werden können. Obwohl noch gewisse Einschränkungen bestehen hinsichtlich der Schnittstellendefinition zwischen den Primitiven oder der Umrechnung von globalen auf lokale Randbedingungen, bietet die Methode eine solide Grundlage für weiterführende Forschungsarbeiten in diesem Bereich.

Unveiling Barriers to Recycling with a Focus on Design: An Ishikawa Diagram-Based Approach with Industrial Application - Rohde, Katharina; Gonzalez, Barbara Fernandez; Budde, Finn Lukas; Ott, Manuel; Mozgova, Iryna; Mendibe, Alain Alonso (Safe and Sustainable Value Creation by Design - Proceedings of the 21st Global Conference on Sustainable Manufacturing)
The circular economy offers decisive advantages over the currently prevalent linear economy in industry. Firstly, the reuse of products, individual parts and material reduces the need for new production or generation and the associated consumption of energy and resources. Secondly, it helps to avoid the generation of waste. Early consideration of circular economic principles in product development processes is essential to specifically promote reuse, reparability and recycling. Efficient recycling of assemblies requires well-defined strategies. However, various challenges hinder the efficiency of technical recycling processes in industrial applications. This paper presents an Ishikawa (fishbone) diagram-based approach to systematically identify and categorize these influences. The method is implemented within an industrial framework, highlighting key obstacles such as material composition, design constraints, use of technology, framework conditions, economic limitations and regulatory challenges. By applying a scenario analysis, this approach examines potential future developments and their impact on recycling-oriented design choices. This helps to identify critical influencing factors and supports the development of resilient and sustainable industrial practices. This framework will serve as the foundation for developing an automated approach to circular design, enabling industries to more effectively integrate sustainability into their processes and adapt to changing environmental demands.

Digital product passports and the challenge of product structure granularity: A decision-making framework for the level of DPP integration - Rohde, Katharina; Budde, Finn Lukas; Patrício, Bárbara; Ferreira, Tânia; Gonçalves, Ana; Ott, Manuel; Mozgova, Iryna (Proceedings of the Design Society)
Political goals, emerging EU sustainability regulations, and industrial digitalization are driving the introduction of Digital Product Passports (DPPs) to enhance transparency, traceability, and compliance across product life cycles. However, the appropriate granularity of DPP integration across product architectures remains ambiguous. This paper introduces a structured, decision-oriented framework that links product structure, regulatory relevance, and information depth to define consistent DPP levels, supporting both industry implementation and future standardization.
Keywords: digital product passport; product architecture; circular economy; information granularity; decision-making framework

Leveraging Large Language Models in Engineering Design and Product Development: A Snapshot - Altun, Osman; Ott, Manuel; Meihöfener, Niclas; Budde, Finn; Mozgova, Iryna (Procedia Computer Science)

Ressourceneffiziente Produktentwicklung: Synergien von Leichtbau und Nachhaltigkeit in Optimierungsprozessen - Mozgova, Iryna; Altun, Osman; Ott, Manuel; Rohde, Katharina (Nachhaltigkeit in der Produktentwicklung)

Fused Deposition Modeling and its Extension Through Metal-Filled Filaments as a Means of Self-Help for Individuals with Physical Disabilities - Ott, Manuel; Jung, Philipp; Bödger, Christian; Mozgova, Iryna; Koch, Rainer; Tröster, Thomas (Innovative Produktentwicklung durch additive Fertigung)

A maturity based data management integration in engineering research projects - Wawer, Max Leo; Müller, Laura; Khaled, Jaouhar Ben; Stauß, Timo; Wurst, Johanna; Mozgova, Iryna; Lachmayer, Roland (Proceedings of the Design Society)
With the increasing amount of data in collaborative engineering research, the need for effective and efficient data management is growing. This paper uses a maturity-based process model to examine the implementation of research data management (RDM) in engineering projects. A process model visualizes a research-supported implementation of RDM and helps researchers evaluate their data management strategies through maturity level assessment. For this approach, activities are assigned to different maturity levels based on a maturity level characteristic providing a differentiated view of the implementation of RDM. An example from an ongoing project shows the application and support of the developed maturity-based process model. The work emphasizes the importance of standardized and quality-assured data management for the success of research projects and their contribution to the scientific community

Getting Things Done: How to Make Simulation Data FAIR and Ready to Reuse - Müller, Laura; Hinterthaner, Marc; Ortlieb, Eduard; Mohnfeld, Norman; Schultz, Andreas Maximilian; Uhe, Johanna; Koepler, Oliver; Mozgova, Iryna (IFIP Advances in Information and Communication Technology)

Strukturierte FDM-Plattformen: Aktuelle Lösungen und Herausforderungen in Informationsinfrastrukturprojekten - Schultz, Andreas Maximilian; Mozgova, Iryna; Altun, Osman; Karras, Oliver; Koepler, Oliver; Müller, Laura; Nuenberger, Florian; Röwenstrunk, Daniel; Wawer, Max Leo

Introduction of electronic lab notebooks in engineering education - opportunities for a cultural change - Müller, Laura; Meihöfener, Niclas; Siemoneit, Johannes Gabriel; Mozgova, Iryna (Engineering Education for Sustainable Development (EESD2025))

Optimierung modularer Produkte für die Mobilität: Ein Klassifizierungsrahmen für zirkuläre Produkte - Rohde, Katharina; Ott, Manuel; Budde, Finn Lukas; Mozgova, Iryna (Solving Conflicts on the Way to Sustainable Mobility: Technische und betriebswirtschaftliche Aspekte)
Für die Aufrechterhaltung der natürlichen Ressourcen ist eine effiziente Nutzung dieser essenziell. Vor diesem Hintergrund untersucht das vorliegende Paper die Rolle der Kreislaufwirtschaft als wegweisendes Wirtschaftsmodell, das von der Europäischen Union gefördert wird. Ziel der Kreislaufwirtschaft ist es, den Ressourcenverbrauch und die Abfallproduktion zu minimieren, indem ein kontinuierlicher Kreislauf aus Nutzung, Wiederverwendung und Recycling von Materialien geschaffen wird. Ein zentraler Aspekt dabei ist der Produktentwicklungsprozess (PEP) - ein vielschichtiger Prozess mit zahlreichen Einflussfaktoren und theoretisch unbegrenzten Gestaltungsmöglichkeiten. Diese Vielfalt führt jedoch zu erheblichen Entscheidungsunsicherheiten, die die Umsetzung von Kreislaufwirtschaftsprinzipien erschweren können. Um diese Herausforderungen zu adressieren, wird ein methodischer Prozess vorgestellt, der eine systematische Klassifizierung im Zusammenhang mit umliegenden Bauteilen ermöglicht. Die Methodik basiert auf einer strukturierten Bewertung von Bauteilen hinsichtlich ihrer Relevanz für die Kreislaufwirtschaft. Dabei werden zentrale Aspekte wie Wiederverwendbarkeit, Recyclingfähigkeit und Ressourceneffizienz berücksichtigt, darunter: • Handelt es sich um ein Gebrauchs- oder Verbrauchsprodukt? • Ist das Bauteil eine Wiederverwendung oder eine Neufertigung? • Ist das Bauteil standardisiert, zugekauft oder individuell ausgerichtet? • Welche primäre Funktion nimmt das Bauteil ein? Diese strukturierte Klassifizierung unterstützt die Entscheidungsfindung bereits früh im PEP. Sie ermöglicht es Produktentwickelnden, Potenziale für die Kreislaufwirtschaft frühzeitig zu erkennen und gezielt nachhaltige Maßnahmen zu ergreifen. Die entwickelte Methodik bildet somit eine Grundlage für die Integration kreislaufwirtschaftlicher Prinzipien in den Entwicklungsprozess. Insbesondere im Kontext moderner Anforderungen des Mobility Management zeigt sich ihr Potenzial, nachhaltige Innovationen gezielt zu fördern und die Umsetzung der Kreislaufwirtschaft in der industriellen Praxis zu erleichtern.

Konzeptionierung eines digitalen Wissensmanagementsystems für die zivile Gefahrenabwehr am Beispiel der Feuerwehr - Schultz, Andreas Maximilian
Wissensmanagement ist im unternehmerischen Kontext ein etabliertes Feld der Forschung und Praxis, das auf die Verbesserung von Effizienz und Wettbewerbsfähigkeit abzielt. In den Organisationen der zivilen Gefahrenabwehr hingegen gibt es erhebliche Defizite bei der Erfassung und Weitergabe von Wissen, obwohl auch hier große Abhängigkeiten vom Erfahrungswissen bestehen. Diese Arbeit analysiert am Beispiel der Feuerwehr die Gründe für diese Diskrepanz und entwickelt ein Konzept, das das Wissensmanagement im Feuerwehrwesen nachhaltig verankern soll. Eine deutschlandweite Umfrage mit 577 Einsatzkräften ergab, dass eine digitale Verwaltungsunterstützung bereits verbreitet ist, das Wissen jedoch vornehmlich per E-Mail, Chat, mündlich oder per Aushang verteilt wird. Die Teilnehmenden wünschen sich eine Lösung für das Wissensmanagement, die im Einsatz, bei Aus- und Weiterbildung sowie der Verwaltungsarbeit unterstützt. Auf der Umfrage und einer systematischen Literaturrecherche aufbauend, wurde der Handlungsbedarf identifiziert. Darauf basieren die Ableitung der Anwendungsbereiche sowie Rahmenbedingungen, welche sich in den Anforderungen an ein Wissensmanagementsystem widerspiegeln. Das Umsetzungskonzept beschreibt die Systemarchitektur der Lösung, die auf einem open-source Wiki mit passenden Erweiterungen beruht. Zentrales Element ist die Möglichkeit zum Austausch von Wissen über Organisationsgrenzen. Abgeschlossen wird die Arbeit mit der Demonstration und Evaluation der Lösung.

Sicherheit bei Großveranstaltungen – Mobilitätsverhalten und Personenströme im Fokus - Schultz, Andreas Maximilian; Dotzki, Fabian; Eisenbach, Thomas; Mozgova, Iryna (Next Chapter in Mobility)

Wissensmanagement in Feuerwehren skalierbare IT-Architektur für Erweiterung und Austausch - Schultz, Andreas Maximilian; Mozgova, Iryna

Requirements Analysis of a Research Data Management System in Collaborative Projects - Müller, Laura; Schultz, Andreas Maximilian; Altun, Osman; Uhe, Johanna; Koepler, Oliver; Auer, Soeren; Mozgova, Iryna (Proceedings of NordDesign 2024)

Handling of uncertainties in the design of sustainable Additive Manufacturing products by merging Design-for-X and Scenario-Technique - Gräßler, Iris; Mozgova, Iryna; Pottebaum, Jens; Ott, Manuel; Jung, Philipp; Hesse, Philipp (17th CIRP Conference on Intelligent Computation in Manufacturing Engineering)
New technologies and materials carry significant potential for sustainable production and use of products. As an example, Additive Manufacturing technologies and materials promise lightweight design and energy efficient use of parts. Exhausting the full potential requires: a) consideration of uncertainties with respect to future capabilities, and b) upgradeable design guidelines to cover advancements consistently. The proposed approach merges concepts of Design-for-X with foresight algorithms of Scenario-Technique to derive actionable knowledge. It is validated by an application in the field of Additive Manufacturing, namely Metal Fused Deposition Modelling. Engineers benefit from the intuitive access to heterogeneous types of sustainability related information.
Keywords: Design-for-X; Scenario-Technique; sustainability; uncertainty; Life-Cycle Engineering; Additive Manufacturing; Circular Economy

Knowledge Management in Civil Protection at the Example of Fire Brigades - Schultz, Andreas Maximilian; Dotzki, Fabian; Mozgova, Iryna (Proceedings of the 16th International Joint Conference on Knowledge Discovery, Knowledge Engineering and Knowledge Management)
Knowledge management is essential for successful disaster management. This paper conducts a Systematic Literature Review at the intersection of the knowledge management field and disaster management and examines the available body of literature. Fire departments are chosen as the focus group as they are the most prevalent emergency services. There are many publications that deal with knowledge management during the response phase of an emergency. Often, the literature focuses on the application of knowledge management in large-scale disasters to link the various organizations on-scene. What is missing in most approaches is a prior step of implementing and training the knowledge management system. Therefore, this literature review seeks to provide an overview of approaches for daily routines and small-to-medium incidents that serve as a training ground. However, literature on non-incident phases and smaller incidents is scarce. As information technologies are developing rapidly, there is no modern and recent description of the current use of knowledge management solutions in this area.
Keywords: Knowledge Management; Civil Protection; Systematic Literature Review; Fire Brigade

An approach to use generic data sets for neural networks in product designs through geometric abstraction via primitives - Ott, Manuel; Meihöfener, Niclas; Mozgova, Iryna (Proceedings of the 11. Conference on Mass Customization and Personalization (MCP))
Generative design suggestions and topology optimizations can help to reduce iterative process loops between calculation and design departments during product development processes. However, precise topology optimizations are computationally intensive, while generative designs benefit from swift suggestions to address design problems efficiently. Using artificial neural networks (ANN) can address this contrast of pre-defined aims by predicting topology-optimized designs, thereby combining both advantageous features. However, a challenge in Mass Customization is, that ANN are usually trained on specific geometries, making transfer to other applications impractical or requiring the creation of new datasets, which is economically unfeasible. Authors have already demonstrated a solution in other publications: dividing a geometry into geometric primitives like cuboids to perform abstraction. An ANN can then be trained to recognize optimized cuboids, which can be assembled back into a complete geometry, comparable to the finite element methods, which divide geometries of parts in finite elements enable mechanical property calculation. This publication aims to illustrate the steps of the approach in which the complete geometry of a part is segmented into these primitives, and the benefits obtained. Various methods will be explored, including automated workflows on modern low-code platforms, to enable generalized use.

State of Knowledge Management among German firefighters - Schultz, Andreas Maximilian; Dotzki, Fabian; Mozgova, Iryna (Proceedings of the 21st ISCRAM Conference)

Prozesskettenorientierte Herstellbarkeitsanalyse von Produkten durch die Nutzung eines Constraint-Satisfaction-Problems - Herrmann, Kevin; Pusch, Felix; Plappert, Stefan; Bode, Behrend; Mozgova, Iryna; Gembarski, Paul Christoph; Lachmayer, Roland (Stuttgarter Symposium für Produktentwicklung SSP 2023: Tagungsband zur Konferenz)
Dieser Beitrag stellt eine rechnergestützte Modellierungsstrategie vor, um Prozesskettenwissen, wie die Gestaltung der Fertigungsstufen, prozessübergreifende Fertigungsrestriktionen oder Fertigungshilfsmittel, für die Produktgestaltung zu formalisieren und im Kontext des Design for Manufacturing für Produkt- und Prozessgestaltungsentscheidungen bereitzustellen. Dabei werden am Beispiel einer Tailored-Forming-Prozesskette die Herstellungsschritte einer Multimaterial-Welle mittels eines Constraint-Satisfaction-Problems (CSP) modelliert, indem die geometrischen Transformationen einzelner Fertigungsstufen sowie Fertigungsrestriktionen in Form von Constraints und Fertigungsstufen sowie Fertigungshilfsmittel über Parameter in den CSP-Variablen formuliert werden. Das CSP ist damit in der Lage, ausgehend von einem Geometriemodell eines Bauteils eine prozesskettenorientierte Restriktionsprüfung zur Herstellbarkeitsbewertung durchzuführen und automatisiert Fertigungsstufen sowie Fertigungshilfsmittel zu konfigurieren.